Involvement of three meningococcal surface‐exposed proteins, the heparin‐binding protein NhbA, the α‐peptide of IgA protease and the autotransporter protease NalP, in initiation of biofilm formation. Issue 2 (4th December 2012) - Arenas, Jesús; Nijland, Reindert; Rodriguez, Francisco J.; Bosma, Tom N. P.; Tommassen, Jan
Summary Neisseria meningitidis is a common and usually harmless inhabitant of the mucosa of the human nasopharynx, which, in rare cases, can cross the epithelial barrier and cause meningitis and sepsis. Biofilm formation favours the colonization of the host and the subsequent carrier state. Two different strategies of biofilm formation, either dependent or independent on extracellular DNA (eDNA), have been described for meningococcal strains. Here, we demonstrate that the autotransporter protease NalP, the expression of which is phase variable, affects eDNA‐dependent biofilm formation in N. meningitidis. The effect of NalP was found in biofilm formation under static and flow conditions and was dependent on its protease activity. Cleavage of the heparin‐binding antigen NhbA and the α‐peptide of IgA protease, resulting in the release of positively charged polypeptides from the cell surface, was responsible for the reduction in biofilm formation when NalP is expressed. Both NhbA and the α‐peptide of IgA protease were shown to bind DNA. We conclude that NhbA and the α‐peptide of IgA protease are implicated in biofilm formation by binding eDNA and that NalP is an important regulator of this process through the proteolysis of these surface‐exposed proteins.